1999
DOI: 10.1063/1.124034
|View full text |Cite
|
Sign up to set email alerts
|

In situ x-ray diffraction study of an electric field induced phase transition in the single crystal relaxor ferroelectric, 92% Pb(Zn1/3Nb2/3)O3–8% PbTiO3

Abstract: We have used in situ x-ray diffraction to measure strain curves of single crystals of 92% Pb(Zn1/3Nb2/3)O3–8% PbTiO3 poled in the 〈001〉 direction. We observed shifts in the (002) and (330) peaks as functions of applied voltage (in the 〈001〉 direction), thereby measuring the crystallographic strain. Our measurements confirm that the high strains observed using macroscopic methods reflect microscopic strains in the crystal lattice. By watching the disappearance of a rhombohedral splitting in the (330) peak, we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
74
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 9 publications
9
74
0
Order By: Relevance
“…Above the threshold field, the strain shows a sharp jump, nonlinear behavior, and hysteresis. X-ray diffraction experiments performed on PZN-8%PT crystals under an applied electric field [11] have shown that the lattice parameter vs field loop exactly reflects the strain behavior, confirming that the high macroscopic strain levels observed are due to the microscopic strain of the crystal lattice. The jump observed at the threshold field was attributed to a structural phase transition between the rhombohedral and the tetragonal phases.…”
Section: (Received 18 September 2000)mentioning
confidence: 60%
See 1 more Smart Citation
“…Above the threshold field, the strain shows a sharp jump, nonlinear behavior, and hysteresis. X-ray diffraction experiments performed on PZN-8%PT crystals under an applied electric field [11] have shown that the lattice parameter vs field loop exactly reflects the strain behavior, confirming that the high macroscopic strain levels observed are due to the microscopic strain of the crystal lattice. The jump observed at the threshold field was attributed to a structural phase transition between the rhombohedral and the tetragonal phases.…”
Section: (Received 18 September 2000)mentioning
confidence: 60%
“…1 (top), after Durbin et al [11]. For this poling configuration, the strain behaves linearly below a certain threshold field, which is smaller for compositions closer to the MPB [8,10].…”
Section: (Received 18 September 2000)mentioning
confidence: 99%
“…The ultrahigh electromechanical response is observed along the <001> direction of the pseudocubic structure in spite of the spontaneous polarisation being along the <111> direction. This effect was related to the occurrence of a rhombohedral to tetragonal phase transition (with polarisation rotation) under the electric field (2). A recent high energy X-ray diffraction study on 0.92PZN-0.08PT crystals has shown that the initial rhombohedral phase first transforms into a monoclinic structure (3).…”
Section: Introductionmentioning
confidence: 99%
“…Previous x-ray investigations have shown that surface damage is a problem in Pbbased perovskites, due to a small x-ray penetration depth ͑m range͒. [1][2][3][4]9 To reduce the surface damage, all faces of every cube were polished to a 0.25 m finish. Polishing resulted in dramatic sharpening of the diffraction peaks.…”
mentioning
confidence: 99%
“…This peak width is close to 3 min obtained by higher energy x-ray sources. [1][2][3][4]9 All three ͗001͘ c faces of the PMN-PT cubes were investigated by -and -scans. The term is the angular position of the sample surface normal in the direction perpendicular to the diffraction plane, whereas is the rotation angle perpendicular to the plane of diffraction.…”
mentioning
confidence: 99%